The underlying mechanism of deficits of speech comprehension and hallucinations in Chinese patients with schizophrenia. (February 2018) - Wang, Jiuju; Wydell, Taeko N.; Zhang, Linjun; Quan, Wenxiang; Tian, Ju; Liu, Jin; Dong, Wentian
Abstract: Sentence context and fundamental frequency (F0) contours are important factors to speech perception and comprehension. In Chinese-Mandarin, lexical tones can be distinguished by the F0 contours. Previous studies found healthy people could use the cue of context to recover the phonological representations of lexical tones from the altered tonal patterns to comprehend the sentences in quiet condition, but can not in noise environment. Lots of research showed that patients with schizophrenia have deficits of speech perception and comprehension. However, it is unclear how context and F0 contours influence speech perception and comprehension in patients with schizophrenia. This study detected the contribution of context and lexical tone to sentence comprehension in four types of sentences by manipulating the context and F0 contours in 32 patients with schizophrenia and 33 healthy controls. The results showed that (1) in patients with schizophrenia, the interaction between context and F0 contour was not significant, which was significant in healthy controls; (2) the scores of sentences with two types of sentences with flattened F0 contours were negatively correlated with hallucination trait scores; (3) the patients with schizophrenia showed significantly lower scores on the intelligibility of sentences in all conditions, which were negatively correlated with PANSS-P. The patients with schizophrenia couldn't use the cue of context to recover the phonological representations of lexical tones from the altered tonal patterns when they comprehend the sentences, inner noise may be the underlying mechanism for the deficits of speech perception and comprehension. Highlights: Schizophrenia can't recover phonological representations of lexical tones from the altered tonal patterns to comprehend sentences. Schizophrenia may have inner noise when they comprehend sentences. The deficits of speech comprehension are correlated with hallucinations in schizophrenia.